Definition of Pharmacovigilance and Its Historical Development in the World and Türkiye - Öztürk Karagöz, Berna (Current Research in Pharmacy and Pharmaceutical Sciences II-2024, 2024)
The unofficial history of pharmacovigilance begins with the proposition expressed in the Hippocratic oath, "Thou shalt do no harm." Since ancient times, human beings have somehow followed every material they used to obtain health, and thousands of years of knowledge have emerged. This journey, which extends from the Sumerians to 19th-century England and from there to humanity's efforts to create a joint memory, has survived to the present day as a highly effective supra-state organization. The concept of pharmacovigilance, which is a shared asset of humankind, has continued to grow and expand its scope with the participation and contribution of our country. Many painful events, which irreversibly changed thousands of lives, occurred during the journey. Our experience, shaped like this, has carried us to this day.This section deals with the definition of pharmacovigilance and its historical development in Türkiye and around the globe. It mentions milestones and events that changed the course in chronological order, and finally, what was needed to prevent tragedies such as the "Thalidomide Disaster" from happening again was expressed.